1865 Fla. Laws 23, 25-27. - (:unkn) unknown (My University, 1866)
An Act Prescribing Additional Penalties for the Commission of Offences against the State, and for Other Purposes, Ch. 1460, No. 3, § 13: That it shall be the duty of the Judge of Probate to keep an accurate register of all licenses so issued as aforesaid, and at each regular meeting of the Board of County Commissioners, to lay the same before them for their supervision, who shall have power to revoke any licenses which, in their opinion, may have been granted to improper persons
Keywords: REGISTRATION